2009
DOI: 10.7205/milmed-d-03-9208
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake and Food Use of Finnish Conscripts in Garrison, on Leave, and in Encampment Conditions

Abstract: At garrison and encampment, nutrient intakes reached recommendations. In free time, conscripts favored energy-rich nutrient-poor foods, which warrants intervening and dietary education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…Its adaptation for our study of young men is not feasible because of our population's homogeneous sex, age and situation-of-life structure. Also, the indices used here were formed based on previous dietary knowledge of a resembling population (25) . Vereecken et al (52) found food indices to correlate with food diary results although overestimation needs to be considered when assessing consumption frequencies from an FFQ.…”
Section: Discussionmentioning
confidence: 99%
“…Its adaptation for our study of young men is not feasible because of our population's homogeneous sex, age and situation-of-life structure. Also, the indices used here were formed based on previous dietary knowledge of a resembling population (25) . Vereecken et al (52) found food indices to correlate with food diary results although overestimation needs to be considered when assessing consumption frequencies from an FFQ.…”
Section: Discussionmentioning
confidence: 99%
“…This food is planned and prepared according to particular military nutrition recommendations for conscripts. It is calculated to cover nutritional requirements of service and offers a varied diet [11]. The menu of the refectories is fixed: lunch and dinner contain one main dish served with fresh or cooked vegetables.…”
Section: Methodsmentioning
confidence: 99%
“…In general, Finnish conscripts’ intakes of energy-yielding nutrients are close to recommendations [7,11]. Still before military service, only 13% of young men consumed daily vegetables and as few as 8% fruits and berries [12].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations